Obtaining Specific Hybridomas for Ki-67 Protein Immunodetection - Aigerim Turgimbayeva; Sailau Abeldenov; Nurgul Sarina; Bekbolat Khassenov; Saule Eskendirova (The Prodia Education and Research Institute (PERI), 2021)
BACKGROUND: Active proliferation is specific property of a tumor cells. However, the cost of the analysis is high due to commercial anti-Ki-67 mAbs used as the main immunoreagent for reliable identification of proliferating cells. In this study, recombinant protein was used to obtain specific mAbs for Ki-67 biomarker immunodetection.METHODS: Codon optimized fragment of ki-67 gene was cloned into the pET28c(+)vector. The recombinant protein was purified by immobilized metal affinity chromatography (IMAC) and confirmed by liquid chromatography–mass spectrometry (LC-MS)/MS. Hybridoma cells were obtained by fusing myeloma cells with mouse spleen cells immunized with recombinant antigen. The specificity and activity of mAbs was determined by enzyme-linked immunosorbent assay (ELISA), Western blot and immunocytochemistry.RESULTS: The pET-28c(+)/ki-67 plasmid, which encodes 355 amino acid protein, was obtained. Analysis by LC-MS/MS of the recombinant antigen showed that 77.5% of the amino-acid sequence belonged to Ki-67 protein. Recombinant fragment of Ki-67 protein was used to obtain specific hybridoma strains. ELISA and Western blot demonstrated high affinity and the specificity of obtained mAbs against Ki-67 protein. Newly generated anti-Ki67 mAbs detected target protein in proliferating cells of MCF-7 cell line by immunocytochemistry.CONCLUSION: Newly developed mAbs are potentially useful as an immunodiagnostic tool for assessing the proliferative activity of breast tumor cells using immunocytochemistry.KEYWORDS: breast cancer, Ki-67, monoclonal antibodies, nuclear antigen, recombinant antigen, tumor cells